2009
DOI: 10.1002/hbm.20516
|View full text |Cite
|
Sign up to set email alerts
|

When do infants differentiate profile face from frontal face? A near‐infrared spectroscopic study

Abstract: The objective of the present study was to determine whether a developmental difference occurs in brain activity when infants look at frontal and profile views using near-infrared spectroscopy (NIRS), which is an optical imaging technique used to measure changes in the concentrations of oxyhemoglobin (oxy-Hb), deoxyhemoglobin (deoxy-Hb), and total hemoglobin (total-Hb). For this objective, we compared NIRS results in two age groups, 5- and 8-month-old infants, while they were looking at frontal views, profile v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
91
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(115 citation statements)
references
References 44 publications
(62 reference statements)
22
91
1
1
Order By: Relevance
“…Jeffreys and Tukmachi (1992) and Rossion and Jacques (2008) showed that upright Arcimboldo images induce a similar pattern of brain activity as faces in adult observers. In the current study, using NIRS, we investigated whether infants show the same brain activity for faces as they do for facial photographs (Honda et al, 2010;Lloyd-Fox, Blasi, & Elwell, 2010;Nakato et al, 2009Nakato et al, , 2011Otsuka et al, 2007) during observation of upright and inverted Arcimboldo images.…”
Section: Introductionmentioning
confidence: 99%
“…Jeffreys and Tukmachi (1992) and Rossion and Jacques (2008) showed that upright Arcimboldo images induce a similar pattern of brain activity as faces in adult observers. In the current study, using NIRS, we investigated whether infants show the same brain activity for faces as they do for facial photographs (Honda et al, 2010;Lloyd-Fox, Blasi, & Elwell, 2010;Nakato et al, 2009Nakato et al, , 2011Otsuka et al, 2007) during observation of upright and inverted Arcimboldo images.…”
Section: Introductionmentioning
confidence: 99%
“…However, the oxy-haemoglobin and total-haemoglobin concentrations in 8-month-old infants increased for both frontal and profile views. These studies suggest that the right temporal hemisphere is specialised for face recognition in infants (Carlsson et al, 2008;Nakato et al, 2011;Nakato et al, 2009;Otsuka et al, 2007). Previous neuroimaging studies in adults also indicated that the right temporal cortex is involved in face recognition.…”
Section: Haemodynamic Responses In Infants During Face Recognitionmentioning
confidence: 92%
“…Haemodynamic changes during the face recognition process as assessed by NIRS have been documented in several studies (Blasi et al, 2007;Csibra et al, 2004;Grossmann et al, 2008;Honda et al, 2010;Ichikawa et al, 2010;Nakato et al, 2009Nakato et al, , 2011aNakato et al, , 2011bOtsuka et al, 2007). Newborns showed a spontaneous preference for face-like stimuli over non-face-like patterns (Fantz, 1961).…”
Section: Haemodynamic Responses In Infants During Face Recognitionmentioning
confidence: 95%
See 2 more Smart Citations